2015
DOI: 10.1093/bioinformatics/btv335
|View full text |Cite
|
Sign up to set email alerts
|

FourCSeq: analysis of 4C sequencing data

Abstract: Motivation: Circularized Chromosome Conformation Capture (4C) is a powerful technique for studying the spatial interactions of a specific genomic region called the ‘viewpoint’ with the rest of the genome, both in a single condition or comparing different experimental conditions or cell types. Observed ligation frequencies typically show a strong, regular dependence on genomic distance from the viewpoint, on top of which specific interaction peaks are superimposed. Here, we address the computational task to fin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
83
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 20 publications
1
83
0
1
Order By: Relevance
“…The zoom-in shows interactions in the SAMD4A TAD (gray rectangle Fig 1D). Few contacts were seen only in the absence of crosslinking (which was also confirmed by a differential analysis via "FourCSeq"; Klein et al, 2015; Appendix Fig S4). Compared to highresolution Hi-C (Rao et al, 2014) and ChIA-PET contact maps (Papantonis et al, 2012) from HUVECs, i4C showed matching interaction profiles and aligned well within TAD boundaries, while also reproducibly detecting some longer-range contacts (Appendix Fig S5A and B).…”
Section: Resultssupporting
confidence: 58%
“…The zoom-in shows interactions in the SAMD4A TAD (gray rectangle Fig 1D). Few contacts were seen only in the absence of crosslinking (which was also confirmed by a differential analysis via "FourCSeq"; Klein et al, 2015; Appendix Fig S4). Compared to highresolution Hi-C (Rao et al, 2014) and ChIA-PET contact maps (Papantonis et al, 2012) from HUVECs, i4C showed matching interaction profiles and aligned well within TAD boundaries, while also reproducibly detecting some longer-range contacts (Appendix Fig S5A and B).…”
Section: Resultssupporting
confidence: 58%
“…S8" type="url"/>) when analysed with FourCseq (Klein et al, 2015). These interactions were marginally reduced in DE.…”
Section: Resultsmentioning
confidence: 99%
“…Sequencing reads were demultiplexed and trimmed of the primer sequence using demultiplex.py from FourCSeq package (Klein et al, 2015), aligned using bowtie2 (v2.2.5) with standard parameters and quality filter set to 1 (-q 1) and processed as described (van de Werken et al, 2012). In short, reads are mapped to a restricted human reference genome (hg19), consisting of sequences directly flanking the 4C primary restriction enzyme site (DpnII), called 4C frag-ends.…”
Section: Methods Detailsmentioning
confidence: 99%